HPLC method development & structural elucidation of antiproliferative quassinoids from Quassia borneensis Noot. (Simaroubaceae) / Julenah Ag Nuddin - Ag Nuddin, Julenah (2016)
Bitter quassinoids have been reported to possess numerous biological activities. They are degraded triterpenoids classified according to their basic skeletons; C₁₈, C₁₉, C₂₀, C₂₂, C₂₅. Currently, more than 200 quassinoids have been isolated from genus Quassia, Brucea, Soulamea, Eurycoma, Picrolemnia and others. A study on Quassia borneensis Noot. (Simaroubaceae) (Qb) for its anti-proliferative active quassinoids using a developed and validated high performance liquid chromatography (HPLC) isolation method is appropriate for data gathering. In addition, a total synthesis exploration of canthin-6-one would provide information regarding its mechanism and influential factors for viability study. The study was accomplished by extracting powdered bark and root Qb by cold maceration and soxhlet in methanol for yield comparison. The methanol extracts were partitioned to acquire n-hexane, chloroform and aqueous fractions. They were tested for their anti-proliferative activity based on MTS assay using HL-60 cell line. Later, chloroform and aqueous fractions were subjected to isolation and purification with HPLC. Then, pure isolates were structurally elucidated with liquid chromatography-mass spectroscopy (LC-MS) and nuclear magnetic resonance (NMR). In addition, the mass profile of active fractions was measured using liquid chromatography-mass spectrometer triple quadrupole time of flight (LC-MSQTOF). Lastly, pure quassinoid compounds were subjected to MTT assay. In a biomimetic total synthesis attempt, canthin-6-one of Simaroubaceae was pursued through carboxyl-mediated approach following the method of Czerwinski et al. (2003). The positively identified sample was collected at Tawai Forest Reserve, Telupid, Sabah, Malaysia. Qb was successfully extracted and partitioned. Later, the anti-proliferative activity of hexane (Q₁-Q₄), chloroform (Q₅-Q₈) and aqueous (Q₉- Q₁₂) fractions were found active except Q₂ while Q₈ was found to be most active at 0.2 |μg/mL…